An Introduction to the Kh̃ler-Ricci Flow - Boucksom, Sebastien.; Eyssidieux, Philippe.; Guedj, Vincent. (Lecture Notes in Mathematics, 2013)
This volume collects lecture notes from courses offered at several conferences and workshops, and provides the first exposition in book form of the basic theory of the Kh̃ler-Ricci flow and its current state-of-the-art. While several excellent books on Kh̃ler-Einstein geometry are available, there have been no such works on the Kh̃ler-Ricci flow. The book will serve as a valuable resource for graduate students and researchers in complex differential geometry, complex algebraic geometry and Riemannian geometry, and will hopefully foster further developments in this fascinating area of research. The Ricci flow was first introduced by R. Hamilton in the early 1980s, and is central in G. Perelman<U+0019>s celebrated proof of the Poincar ̌conjecture. When specialized for Kh̃ler manifolds, it becomes the Kh̃ler-Ricci flow, and reduces to a scalar PDE (parabolic complex Monge-Ampr̈e equation). As a spin-off of his breakthrough, G. Perelman proved the convergence of the Kh̃ler-Ricci flow on Kh̃ler-Einstein manifolds of positive scalar curvature (Fano manifolds). Shortly after, G. Tian and J. Song discovered a complex analogue of Perelman<U+0019>s ideas: the Kh̃ler-Ricci flow is a metric embodiment of the Minimal Model Program of the underlying manifold, and flips and divisorial contractions assume the role of Perelman<U+0019>s surgeries